Food packaging simulant failure mechanisms in next generation steel packaging - Eifion Jewell (Packaging Technology and Science, 2019)
Legislative pressures have led to the mature dominant chromium‐coated steel (ECCS) substrate and epoxy phenolic lacquer replacement in Europe. An investigation was carried out to examine the interaction between a steel surface engineered with a novel, developmental substrate coated using Cr (III)‐based electrolytes and the food stuff being canned. Samples of lacquered material were subjected to a typical retort process (121°C for 90 minutes) and examined using a variety of laboratory analytical techniques. The foodstuff being packaged has a significant impact on the substrate/lacquer adhesion with clear differences in failure mechanisms between foodstuffs. There is clear evidence of chemical species transfer through the next generation lacquer, and this can instigate corrosion at the surface where incomplete chromium coverage leads to exposed iron. In general, the novel developmental material exhibits lower adhesive properties and shows a greater sensitivity to the foodstuff, although this is largely attributed to the homogeneity of the coverage. The novel substrate proves to be a promising alternative to ECCS due to REACH legislation, but improvement is required to achieve equivalent performance.